2013
DOI: 10.1371/journal.pone.0060784
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Inhibits NF-κB Activation in Peripheral Human T Cells

Abstract: The calcineurin inhibitor, tacrolimus (TAC), inhibits the protein phosphatase activity of calcineurin, leading to suppression of the nuclear translocation of NFAT and inhibition of T cell activation. Apart from NFAT also the transcription factor NF-κB plays a key functional role in T cell activation. Therefore, blockade of the NF-κB activation cascade by immunosuppressive drugs prevents immune activation. Here we studied whether TAC blocks NF-κB activation in peripheral human T cells. After anti-CD3/CD28-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 51 publications
(57 reference statements)
1
36
0
1
Order By: Relevance
“…The effect of Tac on the NF-κB activation pathway was studied by quantitative analysis of NF-κB phosphorylation in primary T cell subsets. This study concluded that Tac has a suppressive effect on NF-κB signaling in peripheral T cell subsets [134].…”
Section: Phosphospecific Flow Cytometrymentioning
confidence: 69%
“…The effect of Tac on the NF-κB activation pathway was studied by quantitative analysis of NF-κB phosphorylation in primary T cell subsets. This study concluded that Tac has a suppressive effect on NF-κB signaling in peripheral T cell subsets [134].…”
Section: Phosphospecific Flow Cytometrymentioning
confidence: 69%
“…Both tacrolimus and pimecrolimus selectively inhibit the activation of T cells. 74,75 T cells play a key role in the characteristic inflammation of the skin in eczema. Pimecrolimus has also been trialled as an oral treatment for eczema, which is discussed later in this review (see Chapter 11).…”
Section: Introductionmentioning
confidence: 99%
“…By inhibiting the activity of calcineurin, TAC inhibits the T cell receptor-mediated activation of the nuclear factor of activated T cells (NFAT), one of the key signaling pathways controlling the immune response on a cellular level. In addition to TAC's effect on calcineurin and the NFAT signaling pathway, TAC has recently been described to also affect the NF-κB signaling pathway by inhibiting the phosphorylation of p65 at the serine 529 position (Vafadari et al, 2013). In order to demonstrate the applicability and relevance of IFC to simultaneously evaluate specific phosphorylation motifs and nuclear translocation, TAC exposure of healthy donor T cells was used as the experimental model system with the expectation that TAC induced inhibition of p65 at the serine 529 position should be detectable without affecting nuclear translocation of total p65.…”
Section: Introductionmentioning
confidence: 99%